Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2147/jprls.s180183
|View full text |Cite
|
Sign up to set email alerts
|

<p>Voice treatment in Parkinson’s disease: patient perspectives</p>

Abstract: Speech and voice changes are a central feature of the symptom complex of people with Parkinson's disease (pwPD). Speaking is a social activity involving the pwPD, family, and the wider communicative context. Sensory-motor, cognitive-linguistic, and affective changes in Parkinson's disease (PD) combine to alter communication, impacting on psychosocial quality-of-life, leading to risks of social withdrawal and increased depression and anxiety. The underlying pathophysiology of speech, voice, and communication di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
1
6
0
1
Order By: Relevance
“…The judgments by naïve listeners about expressiveness, ability to discriminate, and perceived communicative effectiveness showed a significant difference between HC participants, whose utterances achieved the highest scores, he PD+ participants, and finally he PD− participants. This data is fully consistent with previous research on this topic, highlighting the speech of PD patients as largely intelligible and ineffective in terms of expressive and communicative competence (Dykstra et al, 2015;Gillivan-Murphy et al, 2019). In this sense, HC subjects were perceived to be more expressive, precise, and effective in communicating emotions than PD+ patients, and considerably more so than PD− patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The judgments by naïve listeners about expressiveness, ability to discriminate, and perceived communicative effectiveness showed a significant difference between HC participants, whose utterances achieved the highest scores, he PD+ participants, and finally he PD− participants. This data is fully consistent with previous research on this topic, highlighting the speech of PD patients as largely intelligible and ineffective in terms of expressive and communicative competence (Dykstra et al, 2015;Gillivan-Murphy et al, 2019). In this sense, HC subjects were perceived to be more expressive, precise, and effective in communicating emotions than PD+ patients, and considerably more so than PD− patients.…”
Section: Discussionsupporting
confidence: 91%
“…This data demonstrates how PD can result in a significant impairment in communicative processes. In particular, these impairments harm the ability to express emotions in a competent and effective way, thus increasing the risk of relational and social barriers from both the perspective of the patient and that of their conversational partners, which can exacerbate the patient's withdrawal from the relational and social dimension (Gillivan-Murphy et al, 2019;Miller, 2017). Measuring expressiveness added some meaningful data to the results from the emotion recognition task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to consider the possibility that speech improvements reported by participants were experienced beyond the voice interaction with VAT. It is widely recognized that there are problems for people with Parkinson disease with maintenance and generalization of speech improvements from therapy tasks into everyday contexts [ 34 ]. The potential for VAT to improve social participation warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study are not in agreement with previous reports, which have indicated that PWPD demonstrated an impaired ability to consistently perceive and identify communication and swallow impairment. Rationale for that impairment was associated with changes to both central and peripheral sensorimotor feedback loops [ 23 , 24 ]. However, we found that a set of questionnaires with questions specific to communication (speech and voice) and swallowing function increased the likelihood that participants would be able to identify impairments…”
Section: Discussionmentioning
confidence: 99%